The Antares maelstrom - Cox, Greg, 1959- (Star Trek: the original series, 2019)
"An epic new Star Trek saga by New York Times bestselling author Greg Cox set during the original Five-Year Mission! The final frontier erupts into chaos as vast quantities of a rare energy source are discovered beneath the surface of Baldur-3, a remote planet beyond the outer fringes of Federation space. Now an old-fashioned "gold rush" is underway as a flood of would-be prospectors, from countless worlds and species, races toward the planet to stake their claim. The galactic stampede threatens the stability of neighboring planets and space stations, as widespread strife and sabotage and all-around pandemonium result in a desperate need for Starfleet assistance. Captain James T. Kirk and the crew of the Starship Enterprise are dispatched to deal with the escalating crisis.